Evaluation of surveillance for Streptococcus suis infection in 5 hospitals in 5 provinces in North region, 2013 - วงศ์คำมา อาทิชา; ฮิ้นจ้อย เสาวพักตร์ (Disease Control Journal, 2015)
Streptococcus suis infection was acquired through consumption of uncooked pork or uncooked pork products or exposure to contaminated pigs or pig’s blood. A case fatality rate ranged from 5.00 to 20.0096. The Streptococcus suis infection had been determined to report under national disease surveillance system since 2011. Evaluation of surveillance for Streptococcus suis infection was to conduct as a cross sectional quantitative study in 5 hospitals in 5 provinces in North region. The objectives were to examine reporting processes of Streptococcus suis infection in the general hospitals and obstacles of the reporting. Data from medical records that met a case definition were retrieved from January 1 to December 31, 2013. Descriptive analyses were performed by Epi Info. There were 460 cases which were enrolled into the study. Of those 460 cases, 67 cases were compatible with the case definition that were defined as 19 suspected cases, 28 probable cases and 20 confirmed cases. Sensitivity of reporting into the national disease surveillance system was 29.89°/o while predictive positive value showing result for 44.4 5 %. Representativeness of age distribution was similar between cases from medical records and cases from the national disease surveillance. An average for timeliness of reporting was 4.9 days. Nurses at screening stations could be the focal person to detect any suspected cases of Streptococcus suis infection when the cases with exposure history admitted to the hospitals. Training course for nurses to gain knowledge about a natural history of Streptococcus suis infection and epidemiology of the disease could be important process to scale up Streptococcus suis infection surveillance. Laboratory surveillance network should also be strengthening to estimate a true incidence of the disease.